2018
DOI: 10.1371/journal.pone.0202176
|View full text |Cite
|
Sign up to set email alerts
|

TAK-272 (imarikiren), a novel renin inhibitor, improves cardiac remodeling and mortality in a murine heart failure model

Abstract: The renin-angiotensin system (RAS), which plays an important role in the progression of heart failure, is efficiently blocked by the inhibition of renin, the rate-limiting enzyme in the RAS cascade. In the present study, we investigated the cardioprotective effects of TAK-272 (SCO-272, imarikiren), a novel, orally effective direct renin inhibitor (DRI), and compared its efficacy with that of aliskiren, a DRI that is already available in the market. TAK-272 was administered to calsequestrin transgenic (CSQ-tg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…In early human clinical trials, doses of 5–200 mg of TAK‐272 were tested in healthy subjects. TAK‐272 at 5 mg per person demonstrated potent and prolonged renin inhibition over 24 h, which was comparable to the effects of 10 mg·kg −1 in triple‐tg mice and the effects of 300 mg·kg −1 in CSQ‐tg mice, as shown in our previous study . This indicates that the effective dose of TAK‐272 in triple‐tg mice was much closer to a clinical dose in humans, than in CSQ‐tg mice.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In early human clinical trials, doses of 5–200 mg of TAK‐272 were tested in healthy subjects. TAK‐272 at 5 mg per person demonstrated potent and prolonged renin inhibition over 24 h, which was comparable to the effects of 10 mg·kg −1 in triple‐tg mice and the effects of 300 mg·kg −1 in CSQ‐tg mice, as shown in our previous study . This indicates that the effective dose of TAK‐272 in triple‐tg mice was much closer to a clinical dose in humans, than in CSQ‐tg mice.…”
Section: Discussionsupporting
confidence: 82%
“…In CSQ‐tg mice, 300 mg·kg −1 of TAK‐272 was required to exert an antihypertrophic effect shown as decrease in LV weight in the present study. Our previous study also indicated that TAK‐272 at 300 mg·kg −1 improved the survival rate of CSQ‐tg mice, but this effect was not significant at 100 mg·kg −1 . On the other hand, we demonstrated that a much lower dose of TAK‐272 (10 mg·kg −1 ) significantly improved cardiac hypertrophy and mortality in triple‐tg mice in the present study.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…52,53 Additionally, they showed cardioprotective activity. 54 Plexxikon: Designed tetrahydroquinoline derivatives with an IC 50 < 10 µM for renin inhibition (Fig. 15).…”
Section: K Ramya Et Al Bioorganic and Medicinal Chemistry XXX (Xxxx)mentioning
confidence: 99%